2002
DOI: 10.1021/ma011726y
|View full text |Cite
|
Sign up to set email alerts
|

Free-Radical Polymerization of Dimethyl Vinylbenzylphosphonate Controlled by Tempo

Abstract: The free radical polymerization of a phosphonated styrene, dimethyl vinylbenzylphosphonate (VBP), in the presence of stable nitroxide 2,2,6,6-tetramethyl-1-piperidinyloxyl radical (TEMPO), initiated by dicumyl peroxide (DCP) at 125 °C, has been studied. The apparent rate of polymerization K p[M•] is eight times higher than that of styrene, but the “living” character of the polymerization could not be verified by SEC. So, a macromolecular initiator PS−TEMPO was used in order to follow the evolution of average n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It was recently shown that radical polymerization controlled by 2,2,6,6-tetramethyl-1-piperidinyloxyl radical (TEMPO) can be applied to produce polystyrene-b-poly (dimethyl vinylbenzylphosphonate) (PS-b-PVBP) block copolymers [26]. Polymerization of a phosphonated styrene VBP initiated by dicumyl peroxide (DCP) at 125 °C in the presence of stable TEMPO has been studied (Scheme 4): the material was further hydrolyzed in order to obtain the amphiphilic property.…”
Section: "Living"/controlled Radical Polymerization Of the Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that radical polymerization controlled by 2,2,6,6-tetramethyl-1-piperidinyloxyl radical (TEMPO) can be applied to produce polystyrene-b-poly (dimethyl vinylbenzylphosphonate) (PS-b-PVBP) block copolymers [26]. Polymerization of a phosphonated styrene VBP initiated by dicumyl peroxide (DCP) at 125 °C in the presence of stable TEMPO has been studied (Scheme 4): the material was further hydrolyzed in order to obtain the amphiphilic property.…”
Section: "Living"/controlled Radical Polymerization Of the Phosphorusmentioning
confidence: 99%
“…Scheme 4 Homopolymerization of styrene or dimethyl vinylbenzylphosphonate (DVBP) [26]. polymerization of phosphorus-containing monomers.…”
Section: "Living"/controlled Radical Polymerization Of the Phosphorusmentioning
confidence: 99%
“…Reversible deactivation radical polymerization (RDRP) technologies such as nitroxide mediated polymerization [48] and atom transfer radical polymerization [49] allow precisely controlled phosphonic esterfunctional polymers to be synthesized. More recently, reversible addition fragmentation chain transfer polymerization (RAFT) [50] and macromolecular design by interchange of xanthates (MADIX) [50] have become the most versatile strategies for the preparation of phosphonated polymers of controlled molar mass and low dispersity [51e55].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, diisopropyl and diethyl p‐ vinylbenzylphosphonate were polymerized by atom transfer radical polymerization. Aminoxyl‐mediated polymerization of diethyl and dimethyl p ‐vinylbenzylphosphonate were also carried out in a controlled manner in the presence of nitroxyl stable radicals.…”
Section: Introductionmentioning
confidence: 99%